2021
DOI: 10.1007/s00423-021-02180-2
|View full text |Cite
|
Sign up to set email alerts
|

Does the non-absorbable suture closure of the jejunal mesenteric defect reduce the incidence and severity of internal hernias after laparoscopic Roux-en-Y gastric bypass?

Abstract: Purpose Internal hernias (IH) are frequent complications after laparoscopic Roux-en-Y gastric bypass (LRYGB). Closure of the jejunal mesenteric and the Petersen defect reduces IH incidence in prospective and retrospective trials. This study investigates whether closing the jejunal mesenteric space alone by non-absorbable suture and splitting the omentum can be beneficial to prevent IH after LRYGB. Methods Observational cohort study of 785 patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
0
2
0
3
Order By: Relevance
“…In the present series, TWL was higher in patients who developed IH. Schneider et al also reported lower BMIs in patients with IH than in the rest of their cohort [33]. With more weight loss, the mesenteries become thinner, which probably facilitates herniation through a small defect.…”
Section: Discussionmentioning
confidence: 82%
“…In the present series, TWL was higher in patients who developed IH. Schneider et al also reported lower BMIs in patients with IH than in the rest of their cohort [33]. With more weight loss, the mesenteries become thinner, which probably facilitates herniation through a small defect.…”
Section: Discussionmentioning
confidence: 82%
“…Devido ao crescente número de pacientes submetidos a ele, os cirurgiões se deparam com altos números de complicações pós-operatórias, dentre elas, o desenvolvimento de HIs. 2,5,7 Este bypass envolve a criação de pequena bolsa gástrica seguida pela divisão do jejuno proximal a 25-50 cm do ângulo duodenojejunal. O jejuno dividido resulta em 2 alças separadas: uma alimentar, também conhecida como membro de Roux, e outra biliopancreática.…”
Section: Discussionunclassified
“…Ainda assim, a literatura indica o fechamento dos defeitos mesentéricos criados, com suturas contínuas não absorvíveis ou com grampos não absorvíveis. 2,4,[7][8][9][10]12 O conhecimento das várias configurações de bypass gástrico (antecólica, retrocólica, bypass gástrico de 1 anastomose), o espectro de aparências de imagem é crucial para esclarecer os defeitos anatômicos específicos observados em estudos de imagem. Efetivamente, sempre haverá dificuldade na interpretação e avaliação das imagens de tomográficas de pacientes pós-bypass gástrico.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The incidence of Petersen’s hernia is quite low, ranging between 1% and 5% ( 4 , 5 ). Such low incidence makes it impossible to conduct prospective studies.…”
Section: Introductionmentioning
confidence: 99%